Radiation-Induced Undifferentiated Pleomorphic Sarcoma after Breast Conserving Therapy: Case Report - Tainara Rodrigues Miranda; Marie Nathalie Chenu; Camila de Carvalho Figueiredo; Marcelo Morais Barbosa; Patricia Chaves de Freitas Campos Jucá (Revista Brasileira de Cancerologia, 2023)
Introduction: Breast sarcoma is a rare form of malignancy that arises from connective tissue, comprising less than 5% of all sarcomas. Undifferentiated pleomorphic sarcoma (UPS) of the breast is a rare and aggressive subtype of radiation-induced sarcoma that can occur in treated breast cancer patients. The diagnosis is challenging and often missed due to the low incidence, long latency period, unspecific imaging finding, and difficulties in clinical and histological detection. Case report: A 56-year-old woman was diagnosed with early-stage triple-negative breast cancer in 2013 and underwent breast-conserving therapy (BCT). After five years follow-up, she developed mastalgia and breast induration, and after mammography and ultrasound without suspicious lesions, a magnetic resonance imaging (MRI) was performed and showed a highly suggestive malignancy mass measuring 8.0 cm and invading the chest wall. The core biopsy revealed a spindle cells malignant tumor, negative for pan cytokeratin and most of immuno-histochemical markers, suggesting sarcoma, but requiring investigation of surgical specimen to exclude metaplastic carcinoma. She underwent Halsted radical mastectomy, full-thickness left anterior chest wall resection contemplating segments of the 4th and 5th ribs and reconstruction with synthetic mesh. The surgical specimen evidenced a UPS with clear margins. The patient had good postoperative recovery and remains in follow-up with the mastology team. Conclusion: This report shows that radiation-induced sarcomas of the breast can be difficult to diagnose, and how later treatment can demand a major surgery with higher morbidity. Prognosis may improve if detected early.